A mathematical model studying mosquito-stage transmission-blocking vaccines - Ruijun Zhao; Jemal Mohammed-Awel (Mathematical Biosciences and Engineering)
A compartmental deterministic model is proposed to evaluatethe effectiveness of transmission-blocking vaccines of malaria, which targets at the parasite stage in the mosquito.The model is rigorously analyzed and numerical simulations are performed.The results and implications are discussed.